IMPLEMENTASI BIMBINGAN KLASIKAL DENGAN PENDEKATAN SOLUSI UNTUK MENCEGAH BURN OUT MAHASISWA - Nurlela; Syska Purnama Sari; Endang Surtiyoni (Counseling Milenial (CM), 2024)
This research aims to explore the implementation of classical guidance with a solution approach as a strategy to prevent burnout in students. Qualitative research methods were used involving students as research subjects. Data was collected through in-depth interviews and participant observation. The research results show that the implementation of classical guidance with a solution approach is effective in helping students manage stress, improve coping, and prevent burnout. Factors such as a good relationship between student and supervisor, social support, and the use of cognitive-behavioral techniques are key to successfully implementing this approach. The practical implication of these findings is the importance of strengthening guidance services in higher education institutions by introducing a solution approach as a potential strategy in preventing burnout in students.